2012
DOI: 10.3109/09546634.2012.672708
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin is safe and efficacious in Asians with acne vulgaris

Abstract: This study reaffirms the overall safety and efficacy of oral isotretinoin in Asian patients with acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Brzezinski et al 61 described hair loss in 154 patients on isotretinoin and commented on its persistence after completing treatment; however, there were no data to support this comment, and the time frame as well as the number of patients affected were unclear. Conversely, a retrospective study by Gan et al 55 reported that hair loss was temporary in 33 patients who experienced hair loss on high-dose isotretinoin.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Brzezinski et al 61 described hair loss in 154 patients on isotretinoin and commented on its persistence after completing treatment; however, there were no data to support this comment, and the time frame as well as the number of patients affected were unclear. Conversely, a retrospective study by Gan et al 55 reported that hair loss was temporary in 33 patients who experienced hair loss on high-dose isotretinoin.…”
Section: Resultsmentioning
confidence: 97%
“…Twenty-two studies (n = 9783 patients) were identified ( Fig 1 , Table I ), 11 , 22 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 17 of which (n = 3940) were included in the frequency analysis summary ( Table II ). One of the studies excluded from frequency analysis did not report the frequency of hair loss and instead quantified the total hair count, hair density, and percentage of hair in the anagen or telogen phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reduction in seborrhea, many of the participating subjects assessed the effect of the laser on sebum reduction as a highly desirable facet of the novel regimen. Moreover, none of the patients developed “uncomfortably dry skin” from the laser treatment, which is commonly observed during oral intake of isotretinoin . Enhancement of both pain‐ and treatment‐related side effects was more remarkable in this novel regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Mild acne resolves without scars, but the severe types may cause permanent scars [ 2 4 ]. Lesions are more common and severe in areas of the skin rich in sebaceous glands [ 5 ]. During puberty, following sebum production, Propionibacterium acne proliferates in the skin and some alterations occur in the follicular epithelial membrane, resulting in closed comedones which are the origin of the subsequent lesions.…”
Section: Introductionmentioning
confidence: 99%